2010
DOI: 10.1144/sp339.6
|View full text |Cite
|
Sign up to set email alerts
|

The land plant cover in the Devonian: a reassessment of the evolution of the tree habit

Abstract: This paper reviews information on the Devonian trees that evolved in the euphyllophyte clade with special focus on the Middle Devonian Pseudosporochnales. The morphology of pseudosporochnalean trees shows analogies with that of extant tree ferns, including the possession of an adventitious root system of limited extent at the base of the trunk. Direct evidence on how these trees were constructed is scarce. We propose a growth model integrating information from younger representatives of the same class known to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 35 publications
1
46
0
Order By: Relevance
“…Whilst an origin from quinone pigments in marine fungi (mainly lignin degraders) or crinoids cannot be excluded, its abundance in the Devonian samples observed here, which coincides with the evolution of the first woody plants and formation of forests (Meyer-Berthaud et al, 2010), points to a likely terrigenous source. Higher plant input was additionally confirmed by palynological and other microscopic evidence which included comminuted plant debris, resin bodies and microfossils from progymnosperms (see Tulipani et al, 2014).…”
Section: Perylene As Indicator Of Terrigenous Inputmentioning
confidence: 63%
“…Whilst an origin from quinone pigments in marine fungi (mainly lignin degraders) or crinoids cannot be excluded, its abundance in the Devonian samples observed here, which coincides with the evolution of the first woody plants and formation of forests (Meyer-Berthaud et al, 2010), points to a likely terrigenous source. Higher plant input was additionally confirmed by palynological and other microscopic evidence which included comminuted plant debris, resin bodies and microfossils from progymnosperms (see Tulipani et al, 2014).…”
Section: Perylene As Indicator Of Terrigenous Inputmentioning
confidence: 63%
“…This resulted in many publications on their morphology, anatomy, palaeoecology, etc. (Beck, 1960;Snigirevskaya, 1984, 2012Meyer-Berthaud et al, 2010 Comparison of the Late Devonian floras of NT with several surrounding ones is based on the analysis of archaeopterideans. We found that all above-described floras of NT contain various archaeopteridean remains.…”
Section: Discussionmentioning
confidence: 99%
“…The situation becomes stranger, the further back in time we retreat. The recent discoveries of weird 'trees' in Devonian strata, including arborescent fungi (Boyce et al 2007) and cladoxylopsids (Stein et al 2007;Meyer-Berthaud et al 2010), well illustrates this point.…”
mentioning
confidence: 82%